Engaging with Everyday Sounds - cobussen, marcel (Open Book Publishers, 2022)
'Engaging With Everyday Sounds' is a rich and inspiring exploration of the role of sounds in everyday life, including their impact on human actions, emotions, and imagination. Marcel Cobussen intertwines sonic studies with philosophy, sound art, sociology and more to create an impressively lucid and innovative guide to sonic materialism, calling for a re-sensitization to our acoustic environment and arguing that everyday sounds have (micro)political, social, and ethical impact to which we should attend. Exploring the intellectual history of sound studies as well as local, global, and temporal sonic geographies, Cobussen weaves audio files, images, and journal excerpts into his work to create a multimodal monograph that explores the relationships of humans, nonhumans, and their environments through sound. This accessible and interdisciplinary collection of short, powerful essays will be valuable reading for both academics and the general reader interested in sound studies, sound art, philosophy, or the sociology of everyday life-and for anyone keen to think about the sonic in new and engaging ways.